Pelaksanaan Jual Beli Pasir Dalam Kajian KHES - Muhammad Arsad Nasution, Sri Hamdani Fitri Siregar & Syafri Gunawan & (Jurnal El-Thawalib, 2020)
Sand is usually taken from rivers and beaches and sold in building shops or directly in sand mining. One of the sand mines is in Binabo Jae Village, the seller takes measurements of the sand using a sheet of truck boards. This study uses a descriptive qualitative approach in data collection used in this study, namely observation, interviews, and documentation. The result of the research states that the measuring instrument for the sale and purchase of sand is carried out using a truck board. The measurement of sand sales is that 3 pieces of truck boards are estimated at 5 cubic meters, 3 pieces of empty truck boards at the front of 1 meter are estimated at 4 cubic meters and 2 pieces of truck boards are estimated at 3 cubic meters. In fact, the width of the truck planks is not the same size resulting in uncertain sand measurements. The sale and purchase of sand in Binabo Jae Village is not fully in accordance with Islamic law and the Compilation of Sharia Economic Laws because the object of sale and purchase results in fasid so that the sale and purchase is declared invalid.